Restructuring of the ‘Macaronesia’ biogeographic unit: a marine multi-taxon biogeographical approach - Freitas, Rui (2019)
The Azores, Madeira, Selvagens, Canary Islands and Cabo Verde are commonly united under the term "Macaronesia". This study investigates the coherency and validity of Macaronesia as a biogeographic unit using six marine groups with very different dispersal abilities: coastal fishes, echinoderms, gastropod molluscs, brachyuran decapod crustaceans, polychaete annelids, and macroalgae. We found no support for the current concept of Macaronesia as a coherent marine biogeographic unit. All marine groups studied suggest the exclusion of Cabo Verde from the remaining Macaronesian archipelagos and thus, Cabo Verde should be given the status of a biogeographic subprovince within the West African Transition province. We propose to redefine the Lusitanian biogeographical province, in which we include four ecoregions: the South European Atlantic Shelf, the Saharan Upwelling, the Azores, and a new ecoregion herein named Webbnesia, which comprises the archipelagos of Madeira, Selvagens and the Canary Islands.